Lietuvių kalbos būtojo kartinio laiko funkciniai atitikmenys anglų kalboje - Steponavičiūtė, I. (Kalbotyra, 1977)
The paper deals with the referential and subjective functions of Lithuanian būtasis kartinis laikas and its functional equivalents in English. The latter can be chosen from among a number of English tenses: Past Indefinite Tense, Past Continuous Tense, Present Perfect Tense, Present Perfect Continuous Tense, Past Perfect Tense, Past Perfect Continuous Tense. Hence, there exists in the English language the possibility of transferring the time relations as well as various shades of meaning expressed by būtasis kartinis laikas more precisely. Būtasis kartinis laikas can be used subjectively, i. e. for an activity or state going on at the moment of speaking or writing, or that which is likely to occur in future. The absence of the corresponding use of past tenses in English makes it necessary to convey the emotional undertone, inherent in the forms of būtasis kartinis laikas thus used, by other lexical or syntactical means. Under certain circumstances past tenses in both languages can indicate courtesy, modesty, humility, and servility on the part of the speaker or, on the other hand, his annoyance, irritation, disapproval, etc. The emotional and affective value of past tenses in both languages is most clearly revealed in the colloquial language, in fiction and, to a lesser degree, in journalistic genre. Elsewhere, i. e. in other functional styles, they are used in their purely objective function.